2020
DOI: 10.1007/s13311-019-00815-3
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 Is a Therapeutic Target and Biomarker in Diazepam-Refractory Status Epilepticus with Wide Time Window

Abstract: Status epilepticus (SE), a life-threatening neurologic emergency, is often poorly controlled by the current pharmacological therapeutics, which are limited to a narrow time window. Here, we investigated the proinflammatory cytokine high mobility group box-1 (HMGB1) as a candidate therapeutic target for diazepam (DZP)-refractory SE. We found that HMGB1 was upregulated and translocated rapidly during refractory SE period. Exogenous HMGB1 was sufficient to directly induce DZPrefractory SE in nonrefractory SE. Neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 60 publications
2
28
0
Order By: Relevance
“…Pre-treatment with mAb 2.5 and mAb 5 decreases the GABA level when compared to the second hit PTZ group. This might be due to the fact that DZP being positive allosteric modulator of the GABA A receptors, HMGB1 decrease the effectiveness of GABA-mediated inhibitory functions ( Zhao et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pre-treatment with mAb 2.5 and mAb 5 decreases the GABA level when compared to the second hit PTZ group. This might be due to the fact that DZP being positive allosteric modulator of the GABA A receptors, HMGB1 decrease the effectiveness of GABA-mediated inhibitory functions ( Zhao et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Taking these results together, we speculate that the HMGB1 released from different sources in response to epileptogenic stimuli may mediate the specific processes leading to status epilepticus, with increased neuronal excitability, including glutamate release, upregulation of IL-1b, TNF-a, TLR-4, and disruption of the BBB [ 21 , 25 , 111 , 112 ]. Moreover, Zhao et al [ 113 ] demonstrated that neutralization of HMGB1 with mAb inhibited a diazepam-resistant status epilepticus model, and this inhibition was mediated by a TLR-4-dependent pathway. Most of the antiepileptics currently available are activators or inhibitors of ion channels in the plasma membrane.…”
Section: Epilepsy and Bbb Disruptionmentioning
confidence: 99%
“…), mice were mounted in a stereotaxic apparatus (512600, Stoelting, United States). Electrodes were implanted into the right hippocampus (AP: −2.9 mm, L: −3.0 mm, V: −3.0 mm) ( Zhao et al, 2020 ). The electrodes were made of twisted stainless steel Teflon-coated wires (diameter 0.2 mm, A.M. Systems, United States) insulated except at the tip (0.5 mm); the tip separation was about 0.5 mm.…”
Section: Methodsmentioning
confidence: 99%